Multilayer Ceramic Capacitors
Patent Information
- Application Number
- JP2024530348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-26
- Filing Date
- 2023-05-11
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2043-05-11
AI Technical Summary
【0011】 この発明によれば、内部電極に含まれるCuTiO3、CoTiO3およびCrTiO3から選ばれる少なくとも1種が、内部電極のカバレージを高めることに寄与する。したがって、内部電極が薄層化されても、内部電極のカバレージが低下せず、積層セラミックコンデンサの大容量化が阻害されないようにすることができる。
Smart Images

Figure 0007635889000005 
Figure 0007635889000001 
Figure 0007635889000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer ceramic capacitor, and more particularly to the composition of internal electrodes provided in the multilayer ceramic capacitor. [Background technology]
[0002] A multilayer ceramic capacitor generally comprises a laminate having a plurality of laminated dielectric layers made of ceramic and a plurality of internal electrodes respectively arranged along a plurality of interfaces between the dielectric layers, and a plurality of external electrodes provided on the outer surface of the laminate and electrically connected to the internal electrodes. The internal electrodes comprise a plurality of first internal electrodes and a plurality of second internal electrodes alternately arranged in the stacking direction of the laminate, and the external electrodes comprise a first external electrode electrically connected to the first internal electrodes and a second external electrode electrically connected to the second internal electrodes.
[0003] In order to miniaturize and increase the capacity of a multilayer ceramic capacitor with such a structure, it is necessary to thin the dielectric layers and internal electrodes and to increase the coverage (electrode continuity) of the internal electrodes. Generally, in the firing process for manufacturing a multilayer ceramic capacitor, the temperature at which the conductive metal particles contained in the conductive paste film that will become the internal electrodes sinter is lower than the temperature at which the ceramic that constitutes the dielectric layers sinters, so the metal particles contained in the internal electrodes sinter first. This causes a decrease in the coverage of the internal electrodes. In particular, in the case of an internal electrode that is thinned to a thickness of 1 μm or less, the coverage is easily decreased, and this decrease in coverage is likely to hinder an increase in capacity.
[0004] Therefore, in order to form a thin internal electrode with high coverage, it is necessary to increase the temperature at which the conductive metal particles contained in the conductive paste film that will become the internal electrode are sintered in the firing process during the manufacture of the multilayer ceramic capacitor. This allows the temperature at which the metal particles contained in the conductive paste film that will become the internal electrode are sintered to be closer to the temperature at which the ceramic that constitutes the dielectric layer begins to sinter, and the timing of contraction during sintering between the internal electrode and the dielectric layer can be brought closer. As a result, the coverage of the internal electrode is increased, and a large capacity can be achieved.
[0005] In order to increase the coverage of the internal electrodes and realize a large capacity by the above-mentioned method, it is known to add a ceramic material having a composition similar to that of the ceramic constituting the dielectric layer, that is, a co-material, to the conductive paste for forming the internal electrodes, as described in, for example, paragraph 0004 of Patent Document 1 (JP Patent Publication No. 2016-31807). By adding the co-material, the sintering timing of the metal particles contained in the conductive paste film to become the internal electrodes can be shifted to a higher temperature, and the temperature at which the metal particles contained in the conductive paste film are sintered can be brought closer to the temperature at which the ceramic constituting the dielectric layer is sintered. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-31807 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, even if a co-material is added to the conductive paste for forming the internal electrodes, it cannot be denied that the temperature at which the metal particles contained in the conductive paste sinter is still lower than the temperature at which the ceramic that constitutes the dielectric layer sinters, and further improvement is desired. In particular, for internal electrodes that are thinned, for example to a thickness of 1 μm or less, there is a strong demand for an effective solution to the problem of reduced coverage that inhibits increased capacity.
[0008] The present invention has been made in view of the above-mentioned problems, and has an object to provide a multilayer ceramic capacitor having internal electrodes which can maintain a relatively high coverage even when the layers are made thin. [Means for solving the problem]
[0009] A multilayer ceramic capacitor according to the present invention includes a laminate having a plurality of laminated dielectric layers made of ceramic, and a plurality of internal electrodes respectively disposed along a plurality of interfaces between the dielectric layers.
[0010] In order to solve the above technical problems, in the present invention, the internal electrodes are made of CuTiO 3 , CoTiO 3 and CrTiO 3 It is characterized by containing at least one selected from the following: Effect of the Invention
[0011] According to the present invention, the CuTiO contained in the internal electrode 3 , CoTiO 3 and CrTiO 3 At least one selected from the group consisting of the above contributes to increasing the coverage of the internal electrodes. Therefore, even if the internal electrodes are made thinner, the coverage of the internal electrodes is not reduced, and it is possible to prevent an increase in the capacitance of the multilayer ceramic capacitor from being hindered. [Brief description of the drawings]
[0012] [Figure 1]1 is a cross-sectional view that typically illustrates a multilayer ceramic capacitor 1 according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The structure of a multilayer ceramic capacitor 1 according to one embodiment of the present invention will be described with reference to FIG.
[0014] The multilayer ceramic capacitor 1 includes a laminate 2. The laminate 2 includes a plurality of laminated dielectric layers 3 made of ceramic, and a plurality of internal electrodes 4 and 5 arranged along the interfaces between the plurality of dielectric layers 3. The internal electrodes 4 and 5 are classified into a plurality of first internal electrodes 4 and a plurality of second internal electrodes 5 arranged alternately in the lamination direction of the laminate 3. A first external electrode 6 and a second external electrode 7 are provided on the outer surface of the laminate 2, more specifically, on each of the opposing end faces. The first external electrode 6 is electrically connected to the first internal electrode 4, and the second external electrode 7 is electrically connected to the second internal electrode 5.
[0015] The dielectric layer 3 is, for example, ABO 3 (A is at least one of Ba, Ca and Sr, and B is at least one of Ti and Zr). The ceramic is made of the above-mentioned ABO 3 The material may contain at least one of Mn, Mg, Si, Y, Dy and Gd as a secondary component.
[0016] The internal electrodes 4 and 5 preferably contain copper as a conductive component. Furthermore, the internal electrodes 4 and 5 have a characteristic composition of CuTiO 3 , CoTiO 3 and CrTiO 3 CuTiO 3 , CoTiO 3 and CrTiO 3 has an ilmenite crystal structure.
[0017] As will be seen from the experimental examples described later, in a preferred embodiment, the dielectric layer 3 is made of BaTiO 3 , SrTiO 3 and CaZrO 3 The internal electrodes 4 and 5 contain copper as a conductive component, and the ceramic material is CuTiO 3 , CoTiO 3 and CrTiO 3 and, if necessary, BaTiO 3 , SrTiO 3 and CaZrO 3 It further comprises at least one selected from the following:
[0018] The external electrodes 6 and 7 are formed, for example, by applying a conductive paste containing Ag or Cu as a main conductive component to the end faces of the laminate 2 and baking the paste. If necessary, for example, Ni plating and Sn plating may be applied on the thick film formed by baking.
[0019] The multilayer ceramic capacitor 1 is manufactured, for example, through the following steps. First, a ceramic slurry containing ceramic raw material powder having the above-mentioned composition is prepared. Next, a suitable sheet forming method is applied to the ceramic slurry to form ceramic green sheets. Next, a conductive paste to be each of the internal electrodes 4 and 5 is applied by printing or the like onto a predetermined ceramic green sheet among the plurality of ceramic green sheets. Next, the plurality of ceramic green sheets are stacked and then pressed together to obtain a green laminate. Next, the green laminate is fired. In this firing step, the ceramic green sheets become the dielectric layers 3. After that, the external electrodes 6 and 7 are formed on the end faces of the laminate 3.
[0020] The conductive paste to become the internal electrodes 4 and 5 used in manufacturing the multilayer ceramic capacitor 1 described above is preferably prepared as follows.
[0021] The conductive paste is produced by carrying out a first step of preparing a ceramic powder slurry containing a ceramic powder, an organic solvent and a dispersant, a second step of preparing a metal powder slurry containing a conductive metal powder, an organic solvent and a dispersant, a third step of preparing an organic vehicle containing an organic resin component and an organic solvent, and a fourth step of mixing the ceramic powder slurry, the metal powder slurry and the organic vehicle.
[0022] More specifically, in the first step, a ceramic powder slurry is prepared by mixing a ceramic powder and a dispersant in an organic solvent.
[0023] The ceramic powder may be, for example, ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 At least one selected from the above is used, and in addition, BaTiO 3 , SrTiO 3 and CaZrO 3 At least one selected from the following may be used.
[0024] When the conductive metal powder contained in the metal powder slurry prepared in the second step described below contains copper, the above-mentioned ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 is the ABO for the ionic radius of copper with six coordinations. 3 The ratio of the ionic radii of the A-site elements in the six-coordination is 0.96 or more and 1.04 or less. 3 The oxide becomes of the type.
[0025] ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3The ceramic powder made of at least one kind selected from the above can suppress a reaction that may occur during firing with the conductive metal powder contained in the metal powder slurry produced in the second step. 3 The oxide may be the main component, and may further contain at least one of Mn, Mg, Si, Y, Dy, and Gd as a secondary component. When such a secondary component is contained, the grain growth of the ceramic particles may be suppressed, and the sintering of the metal particles may be effectively suppressed.
[0026] As the dispersant mixed with the ceramic powder in the first step, for example, an anionic polymer dispersant can be used, and as the organic solvent, for example, dihydroterpineol can be used.
[0027] In the second step, a metal powder slurry is prepared by mixing the conductive metal powder and the dispersant with an organic solvent. The conductive metal powder may be, for example, a powder made of copper or an alloy thereof. The dispersant and organic solvent used in the second step may be the same as those used in the first step.
[0028] In the third step, an organic vehicle is prepared by mixing an organic resin component with an organic solvent. For example, an ethyl cellulose resin can be used as the organic resin component. The organic solvent used in the third step can be the same as that used in the first step.
[0029] In the fourth step, the above-mentioned ceramic powder slurry, metal powder slurry, and organic vehicle are mixed. This results in a conductive paste that will become the internal electrodes 4 and 5. This conductive paste contains a ceramic powder slurry, which, as described above, contains an ABO of a specific ionic radius. 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3Since the ceramic powder contains at least one type of ceramic powder selected from the group consisting of CuTiO 3 , CoTiO 3 and CrTiO 3 It will include at least one selected from:
[0030] [Experimental Example] Next, an example of an experiment carried out to confirm the effects of the present invention will be described.
[0031] In this experimental example, copper powder was prepared as the conductive metal powder contained in the conductive paste for forming internal electrodes.
[0032] On the other hand, the ABO of the specific ion radius that constitutes the ceramic powder contained in the conductive paste for forming the internal electrodes 3 As oxide, CuTiO 3 , CoTiO 3 and CrTiO 3 In addition, BaTiO 3 , CaZrO 3 and SrTiO 3 Table 1 shows these ABO 3 The "crystal structure," "coordination number," "A-site element," and "ionic radius" are shown for the oxides. Note that Ba, Ca, and Sr have 12-coordination in the original perovskite structure, but when Ba, Ca, and Sr dissolve in the sites of the 6-coordination elements (Cu, Co, Cr) in the ilmenite structure, they become 6-coordination, so the "ionic radius" in Table 1 shows the value for 6-coordination.
[0033] [Table 1]
[0034] Below, experimental examples 1, 2, and 3 will be described, which were carried out by changing the ceramic raw material constituting the dielectric layer.
[0035] (Experimental Example 1) Main component of the ceramic that constitutes the dielectric layer: BaTiO 3 1. BaTiO that constitutes the dielectric layer 3 Preparation of ceramic raw materials The starting material is BaCO 3 and TiO 2 Each powder was weighed, mixed in a ball mill for 72 hours, and then heat-treated at a top temperature of 1000°C for 2 hours to obtain a heat-treated powder. 2 O 3 , MgO, SiO 2 and BaCO 3 The powders were prepared as follows: 3 +0.5Mn+1.0Dy+1.0Mg+1.0Si+2.0Ba were weighed out so as to have a composition ratio of +0.5Mn+1.0Dy+1.0Mg+1.0Si+2.0Ba, and these subcomponent powders were added to the heat-treated powder and mixed in a ball mill for 24 hours, then dried to obtain BaTiO 3 Thus, a ceramic raw material powder was obtained.
[0036] 2. Preparation of conductive paste for forming internal electrodes The "ABO 3 oxide" powder and BaTiO for the dielectric layer above 3 The ceramic powder was used as the ceramic powder contained in the conductive paste for forming the internal electrodes.
[0037] These "ABO 3 Oxide" powder and BaTiO 3 The ceramic raw material powders were weighed out to obtain the "addition ratio" shown in Table 2. These powders were premixed with dihydroterpineol as an organic solvent and an anionic polymer dispersant as a dispersant in a media-free agitation mill, and then dispersed in a media agitation mill to produce a ceramic powder slurry (first step).
[0038] On the other hand, copper powder as a conductive metal powder, dihydroterpineol as an organic solvent, and an anionic polymer dispersant as a dispersant were dispersed in a three-roll mill to prepare a metal powder slurry (second process).
[0039] Furthermore, an ethyl cellulose resin as an organic resin component and dihydroterpineol as an organic solvent were mixed together to obtain an organic vehicle (third step).
[0040] Thereafter, the metal powder slurry and the ceramic powder slurry were added to the organic vehicle and mixed and dispersed to prepare a conductive paste for forming internal electrodes (fourth step).
[0041] Table 2 shows the ratio of the ionic radius of the A-site element in 6-coordination to the ionic radius of copper in 6-coordination to be included in the internal electrode, i.e., the "ionic radius ratio (A-site element / metallic copper)." For sample 7, the ratio of the ionic radius of Ba element in 6-coordination (1.35 Å) shown in Table 1 to the ionic radius of copper in 6-coordination (0.77 Å) is shown.
[0042] 3. Fabrication of Multilayer Ceramic Capacitors BaTiO prepared in 1 above 3 A ceramic slurry containing the system ceramic raw material powder was prepared, and then the ceramic slurry was subjected to a doctor blade method to form ceramic green sheets. Next, the conductive paste for forming the internal electrodes prepared in 2 above was applied by screen printing onto a predetermined ceramic green sheet among the plurality of ceramic green sheets. Next, the plurality of ceramic green sheets were stacked and then pressed together to obtain a green laminate. Next, the green laminate was fired. After that, external electrodes were formed on the end faces of the sintered laminate to produce a sample multilayer ceramic capacitor.
[0043] 4. Evaluation
[0044] [Table 2]
[0045] An internal electrode and a dielectric layer located at the center in the height direction of a laminate included in a sample multilayer ceramic capacitor were peeled off from each other by electrochemical peeling.
[0046] Next, the center of the exposed internal electrode (1 / 2 in the width direction and 1 / 2 in the length direction) was observed using a microscope at 100x magnification. The obtained image was then analyzed to determine the percentage of the area of the exposed portion that was occupied by the conductive film as the internal electrode, as the "coverage" shown in Table 2. "Coverage" of 80% or more was judged as good, with a "○" entered in the "Evaluation" column, and "Coverage" of less than 80% was judged as poor, with an "X" entered in the "Evaluation" column.
[0047] 5. Discussion In Table 2, samples 1 to 6 are rated as "○". In these samples 1 to 6, the internal electrodes are ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 The internal electrodes contain copper as a conductive component.
[0048] Here, when we look at the ionic radius, first, "CuTiO 3 As shown in the section "1.4.1.1", the ionic radius of copper in 6-coordination is 0.77 Å. On the other hand, the ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 The ionic radii of the A-site elements in each of the above with 6-coordination are 0.77 Å, 0.74 Å, and 0.80 Å, respectively, as shown in Table 1.
[0049] In samples 1 to 6, which were evaluated as "○", the ABO 3 The ratio of the ionic radii of the A site elements in 6-coordination, i.e., the "ionic radius ratio", is 0.96 or more and 1.04 or less.
[0050] Thus, ABO in samples 1 to 6 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 ABO 3 Since the ionic radius of the A-site element in 6-coordination is equal to or close to the ionic radius of copper in 6-coordination as the conductive metal to be contained in the internal electrode, the energy difference with the copper in the internal electrode becomes zero or small, so that the element remains without being expelled from the internal electrode portion, and acts to improve the heat resistance of the internal electrode. As a result, it is presumed that the coverage was high at 84% or more in samples 1 to 6.
[0051] In addition, as in samples 4 to 6, CuTiO 3 , CoTiO 3 and CrTiO 3 The addition ratio of CuTiO is not necessarily 100%, but as long as it is 10% or more, 3 , CoTiO 3 and CrTiO 3 In Experimental Example 1, the effect of improving coverage was observed compared to the case where none of CuTiO 3 , CoTiO 3 and CrTiO 3 It is also noteworthy that the coverage of samples 4 to 6, which have an addition ratio of 10%, shows values equal to the coverage of samples 1 to 3, which have an addition ratio of 100%.
[0052] In contrast, sample 7, which was rated as "x", had BaTiO 3 In this case, only ABO with a perovskite structure is added to the internal electrodes. 3Ba, the A-site element in the ilmenite structure, has 12 coordination numbers, but when it dissolves in the A-site of the ilmenite structure, it is necessary to compare the ionic radius at 6 coordination numbers, which is the coordination number of the A-site of the ilmenite structure, and the ionic radius of Ba at 6 coordination numbers is 1.35 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Ba at 6 coordination numbers to the ionic radius of copper at 6 coordination numbers, that is, the "ionic radius ratio", is 1.75. Therefore, the "ionic radius ratio" is outside the range of 0.96 to 1.04, and the coverage was low at 74%.
[0053] In sample 7, the "ionic radius ratio" is outside the range of 0.96 to 1.04, and BaTiO 3 It is presumed that this is because the heat resistance of the internal electrode was not improved and the coverage was reduced.
[0054] (Experimental Example 2) Main component of the ceramic that makes up the dielectric layer: CaZrO 3 1. CaZrO that constitutes the dielectric layer 3 Preparation of ceramic raw materials The starting material is the main component CaCO 3 and ZrO 2 Each powder, as well as the sub-components MnO and SiO 2 The powders of CaZrO and MgO were weighed and mixed in a ball mill for 72 hours, and then heat-treated at a top temperature of 1000°C for 2 hours to obtain CaZrO 3 Thus, a ceramic raw material powder was obtained.
[0055] 2. Preparation of conductive paste for forming internal electrodes The "ABO 3 Oxide" powder and CaZrO for the above dielectric layer 3 The ceramic powder was used as the ceramic powder contained in the conductive paste for forming the internal electrodes.
[0056] These "ABO 3 Oxide" powder and CaZrO 3The ceramic raw material powders and the base ceramic powder were weighed out so as to obtain the "addition ratio" shown in Table 3, and a conductive paste for forming internal electrodes was produced through the same steps as in the above Experimental Example 1.
[0057] Table 3 shows the "ionic radius ratio (A-site element / metallic copper)" as in Table 2. For sample 17, the ratio of the ionic radius of Ca element in 6-coordination (1.00 Å) shown in Table 1 to the ionic radius of copper in 6-coordination (0.77 Å) is shown.
[0058] 3. Fabrication of Multilayer Ceramic Capacitors CaZrO prepared in 1 above 3 A ceramic slurry containing the ceramic raw material powder was prepared, and then the ceramic slurry was formed into ceramic green sheets by a doctor blade method. After that, a multilayer ceramic capacitor sample was prepared through the same steps as in Experimental Example 1.
[0059] 4. Evaluation
[0060] [Table 3]
[0061] Following the same procedure as in Experimental Example 1, the "coverage" was determined as shown in Table 3 and evaluated in the same manner.
[0062] 5. Discussion In Table 3, samples 11 to 16 are rated as "○". In these samples 11 to 16, the internal electrodes are ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 The internal electrodes contain copper as a conductive component.
[0063] Here, when we look at the ionic radius, first, "CuTiO 3As shown in the section "1.4.1.1", the ionic radius of copper in 6-coordination is 0.77 Å. On the other hand, the ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 The ionic radii of the A-site elements in each of the above with 6-coordination are 0.77 Å, 0.74 Å, and 0.80 Å, respectively, as shown in Table 1.
[0064] In samples 11 to 16, which were evaluated as "○", the ABO 3 The ratio of the ionic radii of the A site elements in 6-coordination, i.e., the "ionic radius ratio", is 0.96 or more and 1.04 or less.
[0065] Thus, the ABO in samples 11 to 16 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 ABO 3 Since the ionic radius of the element in the A site in 6-coordination is equal to or close to the ionic radius of copper in 6-coordination as the conductive metal to be contained in the internal electrode, the energy difference with the copper in the internal electrode is zero or small, so that the element remains without being expelled from the internal electrode portion and acts to improve the heat resistance of the internal electrode. As a result, it is presumed that the coverage was high at 81% or more in samples 11 to 16.
[0066] In addition, as in samples 14 to 16, CuTiO 3 , CoTiO 3 and CrTiO 3 The addition ratio of CuTiO is not necessarily 100%, but as long as it is 10% or more, 3 , CoTiO 3 and CrTiO 3 The effect of improving coverage was observed compared to when none of the above was included.
[0067] In contrast, sample 17, which was rated as "x", had CaZrO3 In this case, only ABO with a perovskite structure is added to the internal electrodes. 3 In the above, Ca, which is the A-site element, has 12 coordination numbers, but when it dissolves in the A-site of the ilmenite structure, it is necessary to compare the ionic radius at 6 coordination numbers, which is the coordination number of the A-site of the ilmenite structure, and the ionic radius of Ca at 6 coordination numbers is 1.00 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Ca at 6 coordination numbers to the ionic radius of copper at 6 coordination numbers, that is, the "ionic radius ratio", is 1.30. Therefore, the "ionic radius ratio" is outside the range of 0.96 or more and 1.04 or less, and the coverage was low at 72%.
[0068] In sample 17, the "ionic radius ratio" was outside the range of 0.96 to 1.04, and the CaZrO 3 It is presumed that this is because the heat resistance of the internal electrodes was not improved and the coverage was reduced.
[0069] (Experimental Example 3) Main component of the ceramic that makes up the dielectric layer: SrTiO 3 1. SrTiO that constitutes the dielectric layer 3 Preparation of ceramic raw materials The starting material is the main component SrCO 3 and TiO 2 Each powder, as well as the sub-components MnO and SiO 2 and MgO powders were weighed and mixed in a ball mill for 72 hours, and then heat-treated at a top temperature of 1000°C for 2 hours to obtain SrTiO 3 Thus, a ceramic raw material powder was obtained.
[0070] 2. Preparation of conductive paste for forming internal electrodes The "ABO 3 SrTiO powder for the dielectric layer and SrTiO 3 The ceramic powder was used as the ceramic powder contained in the conductive paste for forming the internal electrodes.
[0071] These "ABO 3Oxide" powder and SrTiO 3 The ceramic raw material powders and the base ceramic powder were weighed out so as to obtain the "addition ratio" shown in Table 4, and a conductive paste for forming internal electrodes was produced through the same steps as in the above Experimental Example 1.
[0072] Table 4 shows the "ionic radius ratio (A-site element / metallic copper)" as in Table 2. For sample 27, the ratio of the ionic radius of Sr element in 6-coordination (1.18 Å) shown in Table 1 to the ionic radius of copper in 6-coordination (0.77 Å) is shown.
[0073] 3. Fabrication of Multilayer Ceramic Capacitors The SrTiO prepared in 1 above 3 A ceramic slurry containing the ceramic raw material powder was prepared, and then the ceramic slurry was formed into ceramic green sheets by a doctor blade method. After that, a multilayer ceramic capacitor sample was prepared through the same steps as in Experimental Example 1.
[0074] 4. Evaluation
[0075] [Table 4]
[0076] Following the same procedure as in Experimental Example 1, the "coverage" was determined as shown in Table 4 and evaluated in the same manner.
[0077] 5. Discussion In Table 4, samples 21 to 26 are rated as "○". In these samples 21 to 26, the internal electrodes are ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 The internal electrodes contain copper as a conductive component.
[0078] Here, when we look at the ionic radius, first, "CuTiO 3As shown in the section "1.4.1.1", the ionic radius of copper in 6-coordination is 0.77 Å. On the other hand, the ABO 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 The ionic radii of the A-site elements in each of the above with 6-coordination are 0.77 Å, 0.74 Å, and 0.80 Å, respectively, as shown in Table 1.
[0079] In samples 21 to 26, which were evaluated as "○", the ABO 3 The ratio of the ionic radii of the A site elements in 6-coordination, i.e., the "ionic radius ratio", is 0.96 or more and 1.04 or less.
[0080] Thus, the ABO in samples 21 to 26 3 CuTiO as oxide 3 , CoTiO 3 and CrTiO 3 ABO 3 Since the ionic radius of the element in the A site in 6-coordination is equal to or close to the ionic radius of copper in 6-coordination as the conductive metal to be contained in the internal electrode, the energy difference with the copper in the internal electrode is zero or small, so that the element remains without being expelled from the internal electrode portion and acts to improve the heat resistance of the internal electrode. As a result, it is presumed that the coverage was high at 80% or more in samples 21 to 26.
[0081] In addition, as in samples 24 to 26, CuTiO 3 , CoTiO 3 and CrTiO 3 The addition ratio of CuTiO is not necessarily 100%, but as long as it is 10% or more, 3 , CoTiO 3 and CrTiO 3 The effect of improving coverage was observed compared to when none of the above was included.
[0082] In contrast, sample 27, which was rated as "x", had SrTiO3 In this case, only ABO with a perovskite structure is added to the internal electrodes. 3 Sr, the A-site element in the ilmenite structure, has 12 coordination numbers, but when it dissolves in the A-site of the ilmenite structure, it is necessary to compare the ionic radius at 6 coordination numbers, which is the coordination number of the A-site of the ilmenite structure, and the ionic radius of Sr at 6 coordination numbers is 1.18 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Sr at 6 coordination numbers to the ionic radius of copper at 6 coordination numbers, that is, the "ionic radius ratio", is 1.53. Therefore, the "ionic radius ratio" is outside the range of 0.96 to 1.04, and the coverage was low at 70%.
[0083] In sample 27, the "ionic radius ratio" was outside the range of 0.96 to 1.04, and SrTiO 3 It is presumed that this is because the heat resistance of the internal electrode was not improved and the coverage was reduced.
[0084] In the above-described experimental examples 1 to 3, copper powder was used as the conductive metal powder contained in the conductive paste for forming internal electrodes.
[0085] However, the ionic radius of the six-coordinated conductive metal elements in the internal electrodes is CuTiO 3 , CoTiO 3 and CrTiO 3 As long as the relationship of being equal to or greater than (1 / 1.04) and equal to or smaller than (1 / 0.96) of the ionic radius of the A site element in 6-coordination is satisfied, a metal other than copper may be used as the conductive metal contained in the internal electrodes.
[0086] The embodiments of the present invention include the following.
[0087] <1> A laminate having a plurality of laminated dielectric layers made of ceramic and a plurality of internal electrodes respectively disposed along a plurality of interfaces between the dielectric layers, The internal electrodes are CuTiO 3 , CoTiO3 and CrTiO 3 At least one selected from Multilayer ceramic capacitor.
[0088] <2> The internal electrodes contain copper as a conductive component. <1> The multilayer ceramic capacitor according to claim 1 .
[0089] <3> The internal electrodes have a thickness of 1 μm or less. <1> or <2> The multilayer ceramic capacitor according to claim 1 .
[0090] <4> The internal electrodes have a coverage of 80% or more. <1> Or <3> 2. The multilayer ceramic capacitor according to claim 1 .
[0091] <5> The dielectric layer is BaTiO 3 , SrTiO 3 and CaZrO 3 The internal electrodes are made of ceramics mainly composed of at least one selected from the group consisting of BaTiO 3 , SrTiO 3 and CaZrO 3 Further comprising at least one selected from <1> Or <4> 2. The multilayer ceramic capacitor according to claim 1 . [Explanation of symbols]
[0092] 1. Multilayer ceramic capacitors 2. Laminate 3 Dielectric Layer 4,5 Internal electrode 6,7 External electrode
Claims
1. A laminate having a plurality of laminated dielectric layers made of ceramic and a plurality of internal electrodes respectively disposed along a plurality of interfaces between the dielectric layers, The internal electrodes are CuTiO 3 , CoTiO 3 and CrTiO 3 At least one selected from Multilayer ceramic capacitor.
2. 2. The multilayer ceramic capacitor according to claim 1, wherein the internal electrodes contain copper as a conductive component.
3. 2. The multilayer ceramic capacitor according to claim 1, wherein the internal electrodes have a thickness of 1 μm or less.
4. 4. The multilayer ceramic capacitor according to claim 1, wherein said internal electrodes have a coverage of 80% or more.
5. The dielectric layer is BaTiO 3 , SrTiO 3 and CaZrO 3 The internal electrodes are made of ceramics mainly composed of at least one selected from the following: 3 , SrTiO 3 and CaZrO 3 4. The multilayer ceramic capacitor according to claim 1, further comprising at least one selected from the following:
Citation Information
Patent Citations
JP1974056822A
Conductive paste and laminated electronic component, and their manufacturing method
JP2001284162A
Conductive paste composition for internal electrode and multilayer ceramic electronic component including the same
JP2013214698A
Method for producing composite powder and conductive thick film paste and multilayer ceramic electronic component using composite powder obtained by the production method
JP2015083714A
Conductive paste and production method of the same
JP2016031807A